Critical Analysis of ‘Aql and Brain in the Paradigm of the Qur’an and Neuroscience and Its Contribution to the Development of Islamic Education - Mohammad Jailani; Suyadi; Nur Kholis; Miftachul Huda (Universitas Ahmad Dahlan, 2023)
The purpose of this study was to analyze the meaning of nāṣiyah in Tafsir Salman from a neuroscience perspective. The development of neuroscience and Islamic education in this modern era is in line with the emergence of new findings, namely research about the meaning (nāṣiyah) in the Qur’an which some commentators define as “the crown” or in the neuroscience perspective behind the crown, namely the prefrontal cortex. The data of this research are sourced from literature studies through manual and digital searches, focusing on the Nāṣiyah interpretation paradigm in Surah Al-Alaq verses 15-16. The results of the study show that the meaning of nāṣiyah is identical to the meaning (forehead). In Salman's interpretation, what is meant by the crown is the brain, especially the prefrontal cortex. Therefore, nāṣiyah is a neurobiological trace of the brain in the Qur’an. The discovery of the concept of nāṣiyah as the neurobiological basis of the brain in the Qur’an will have broad implications for the development of the potential of ‘aql (reason) in Islamic education. The essence of Islamic education, one of which is the development of the potential of reason as a manifestation of brain function (nāṣiyah) in the Koran.